GROWTH AND PRODUCTION PERFORMANCE OF SAND LOBSTER (Panulirus homarus) CULTURED IN FLOATING NET CAGES - Manta Prayanti; Indra Lesmana; Kristina Kristina; Rusliadi Rusliadi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Riau, 2026)
Sand lobster (Panulirus homarus) is a high-value marine commodity with promising potential for mariculture development in Indonesia. This study described the grow-out technique for P. homarus in floating net cages at BPBL Batam. It evaluated its production performance in terms of growth, feed utilization, survival, and water quality. A field-based observational study was conducted for 74 days using juveniles with an initial mean body weight of 5.14 g and an initial mean total length of 5.44 cm. Lobsters were reared in six submerged M-sized cages (0.7 m² per unit) at a stocking density of 50 individuals per cage and were fed chopped trash fish once daily at 20% of biomass. Mean body weight and total length increased to 20.94 g and 8.47 cm, respectively, with absolute weight gain of 15.80 g, absolute length gain of 3.03 cm, and a specific growth rate of 1.89% day⁻¹. However, the feed conversion ratio was high (30.00), and the survival rate was low (40.33%). Water-quality variables remained within acceptable ranges for lobster culture. These findings indicate that the system supported lobster growth, but feed-use efficiency and survival still require improvement through better feeding and husbandry management.